PENGARUH PENGETAHUAN INVESTASI DAN MODAL MINIMAL TERHADAP MINAT INVESTASI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PANCASAKTI TEGAL - Umi, Mas'ulah; Fenti, Nurlaeli; Agung Setia, Budi (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
FEB UPS Tegal students in direct practice involved in capital market investment are quite low and rigid in carrying out investment transactions. This research aims to determine the effect of investment knowledge and minimum investment capital on students' investment interest in the capital market. The research method used is quantitative descriptive, using primary data, namely questionnaires. The test uses validity and reliability tests, and data analysis techniques use the classical assumption test, multiple linear regression analysis. The results of this research show that it is valid and reliable. The value of t calculated for knowledge is 4.165 > t table 1.985, meaning it influences investment interest, value, t calculated minimum capital 2.680 > t table 1.985, meaning it influences investment interest, knowledge value and minimum capital, F calculated 42.052 > F table 3.09 meaning simultaneously influences investment interest in the capital market. Students are expected to be able to apply the basic investment knowledge they have acquired so that the knowledge they have gained is not just theoretical. IDX is expected to socialize Let's Save Stocks at other universities.